Military Leadership in Business: An Analysis of its Role and Impact in Indonesia - Gerry Juan Carlos; Tri Widyastuti; Adler Haymans Manurung; Hasanuddin Hasanuddin (Journal of Law, Politic and Humanities, 2025)
This study examines the role and impact of military leadership in the business sector in Indonesia, an important topic amidst the growing number of former military personnel occupying leadership positions in companies. The primary objective of this research is to analyze how military leadership styles are applied in business contexts and their impact on organizational performance. The research questions include: What is the role of military leadership in the business sector? What is its impact on business organizational performance? This research uses a qualitative approach with a case study design and in-depth interviews as data collection techniques. The data were analyzed using thematic analysis to identify key patterns and themes. The findings indicate that military leadership significantly contributes to organizational discipline and efficiency but faces challenges in flexibility and innovation. The conclusion of this research highlights the importance of adapting military leadership to the dynamic business environment and provides suggestions for further in-depth research.